Vertebrates As Bioindicators of Climate Change - Yevheniia Yanish (Емінак, 2023)
The use of living organisms for stratigraphy or as bioindicators of the state of the environment has been known since the 19th century, but mainly for these studies the remains of invertebrate animals (in particular, molluscs) are used, and from vertebrates – mouse-like rodents. In the course of the work, certain species of vertebrates and invertebrates were selected, based on the presence of which in the material it is possible to reconstruct the climatic conditions in the historical past. Such information is very important for historians and archaeologists, since it allows them to better understand the living conditions of people in the historical past.